Glomerulonephritis and Nephrotic Syndrome 2019
DOI: 10.5772/intechopen.86489
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in Renal Vasculitis

Abstract: The use of biomarkers in glomerular diseases has been subject of investigation during the last decades, as it can provide worthwhile evidence in diagnosis, but also, it can guide treatment and give information about prognosis and response. Renal biopsy is still the compulsory technique to establish diagnosis, and also to offer information about the severity of renal damage. However, as an invasive method, it cannot be regularly performed during follow up, so the need to find and establish measurement of molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
(163 reference statements)
0
2
0
Order By: Relevance
“…In patients with IgA vasculitis (IgAV), increased serum levels of poorly galactosylated IgA1 remain the most consistent finding in patients with IgA nephritis and IgA nephropathy [7]. Renal biopsy is essential for diagnosing IgAV-N, probably guiding treatment and predicting outcome; the procedure cannot be used repeatedly during patient follow-up [31]. In patients with active AAV, there were significantly higher urinary levels of Bb, C3a, C5a, and soluble C5b-9 [20].…”
Section: Immunoglobulins and Complementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with IgA vasculitis (IgAV), increased serum levels of poorly galactosylated IgA1 remain the most consistent finding in patients with IgA nephritis and IgA nephropathy [7]. Renal biopsy is essential for diagnosing IgAV-N, probably guiding treatment and predicting outcome; the procedure cannot be used repeatedly during patient follow-up [31]. In patients with active AAV, there were significantly higher urinary levels of Bb, C3a, C5a, and soluble C5b-9 [20].…”
Section: Immunoglobulins and Complementsmentioning
confidence: 99%
“…However, serum sCD163 levels failed to distinguish infections from active disease, which may limit its use [40]. A multicenter study showed that urinary CD89 and transglutaminase2 (TG2) concentrations are significantly lower in patients with active IgA vasculitis and nephritis compared to individuals whose disease has gone into complete or partial remission [31]. Incomplete B-cell depletion and repopulation after treatment with rituximab have been associated with a significantly higher rate of relapses in AAV patients [41].…”
Section: B Cells T Cells Cytokines Chemokines-serum and Urinementioning
confidence: 99%